Admittance‐based pressure–volume loops versus gold standard cardiac magnetic resonance imaging in a porcine model of myocardial infarction. Issue 4 (23rd April 2014) - van Hout, Gerardus P. J.; Jansen of Lorkeers, Sanne J.; Gho, Johannes M. I. H.; Doevendans, Pieter A.; van Solinge, Wouter W.; Pasterkamp, Gerard; Chamuleau, Steven A. J.; Hoefer, Imo E.
Abstract: A novel admittance‐based pressure–volume system (AS) has recently been developed and introduced. Thus far, the new technique has been validated predominantly in small animals. In large animals it has only been compared to three‐dimensional echocardiography (3DE) where the AS showed to overestimate left ventricular (LV) volumes. To fully determine the accuracy of this device, we compared the AS with gold standard cardiac magnetic resonance imaging (CMRI) in a porcine model of chronic myocardial infarction (MI). Fourteen pigs were subjected to 90 min closed chest balloon occlusion of the left anterior descending artery. After 8 weeks of follow up, pigs were consecutively subjected to LV volume measurements by the AS, CMRI, and 3DE under general anesthesia. The AS overestimated end diastolic volume (EDV; +20.9 ± 30.6 mL, P = 0.024) and end systolic volume (ESV; +17.7 ± 29.4 mL, P = 0.042) but not ejection fraction (EF; +2.46 ± 6.16%, P = NS) compared to CMRI. Good correlations of EDV ( R = 0.626, P = 0.017) and EF ( R = 0.704, P = 0.005) between the AS and CMRI were observed. EF measured by the AS and 3DE also correlated significantly ( R = 0.624, P = 0.030). After subjection of pigs to MI, the AS very moderately overestimates LV volumes and shows accurate measurements for EF compared to CMRI. This makes the AS a useful tool to determine cardiac function and dynamic changes in large animal models of cardiac disease. Abstract : e00287 Is the novel admittance‐based pressure–volume loop system reliable for the assessment of left ventricular volumes compared to gold standard cardiac magnetic resonance imaging in a porcine model of myocardial infarction? In the postinfarction remodeled heart, admittance‐based pressure–volume loop measurements accurately measure ejection fraction and very moderately overestimate end diastolic and end systolic volumes compared to gold standard cardiac magnetic resonance imaging, making it a very useful technique for cardiac function assessment in experimental studies.